Implications of the Russia-Ukraine war on India’s agrifood systems and policy responses - Ritter, Thea; Mockshell, Jonathan; Blanco, Maria (2023)
This policy brief examines consequences of the Russia-Ukraine war on India’s agrifood systems, focusing on impacts on staple foods and agricultural inputs, as well as the Government of India’s policy responses to the war. The methodology is based on content analysis of articles, published papers, reports, and official announcements, in addition to analyzing data from a variety of international and Government of India sources. India plays a critical role in global agricultural production. The Russia-Ukraine war has cast a shadow over India's food security landscape, particularly within rural areas where inflation's disproportionate impact on food and nutritional security is evident. The war has ushered in escalating fuel and fertilizer prices, which, given India's reliance on imports, has reverberated adversely throughout the agricultural sector. In response to the impacts of the war, the Indian government has taken various measures, including a recent export ban on non-basmati rice, an export ban on broken rice, an import tariff for rice, cuts in excise duty on diesel and petrol, an increase in the production of organic and inorganic fertilizers, and the implementation of a fertilizer subsidy. Strengthening the resilience of India’s agrifood systems is a priority, emboldened by the National Food Security Mission.